2005
DOI: 10.1007/s10439-005-3237-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Closing Sounds of a Mechanical Heart Valve

Abstract: In the 1994 Replacement Heart Valve Guidance of the U.S. Food and Drug Administration (FDA), in-vitro testing is required to evaluate the potential for cavitation damage of a mechanical heart valve (MHV). To fulfill this requirement, the stroboscopic high-speed imaging method is commonly used to visualize cavitation bubbles at the instant of valve closure. The procedure is expensive; it is also limited because not every cavitation event is detected, thus leaving the possibility of missing the whole cavitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a previous study by the authors, we investigated the valve closing sound in air, naturally without the presence of cavitation. 25 It was found that the frequency of the closing sound of a Bjö rk-Shiley Convexo-Concave valve can reach as high as 123 Ϯ 6 kHz, with 99% of the total sound energy being accounted for, which is close to the 100 kHz value observed by Herman et al 26 on a 27-mm Medtronic Hall tilting disc valve under noncavitating conditions in water. These results indicate that the mechanical closing sound of an MHV might contain frequencies higher than what were previously thought.…”
mentioning
confidence: 62%
“…In a previous study by the authors, we investigated the valve closing sound in air, naturally without the presence of cavitation. 25 It was found that the frequency of the closing sound of a Bjö rk-Shiley Convexo-Concave valve can reach as high as 123 Ϯ 6 kHz, with 99% of the total sound energy being accounted for, which is close to the 100 kHz value observed by Herman et al 26 on a 27-mm Medtronic Hall tilting disc valve under noncavitating conditions in water. These results indicate that the mechanical closing sound of an MHV might contain frequencies higher than what were previously thought.…”
mentioning
confidence: 62%
“…The electronic transducer can digitally record HS, laying the groundwork for subsequent processing and application of HS signal. Furthermore, HS can directly reflect the property of cardiac mechanical activity and provide useful information for early diagnosis of cardiac abnormalities [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups have suggested that high-intensity transient pressure detected by ultrasonography was useful as an indication of cavitation intensity (8)(9)(10)(11)(12). The frequency of the pressure signal when cavitation bubbles collapse has been investigated using a pressure sensor or hydrophone, but the results varied widely (13)(14)(15). However, these experiments were performed under nonsynchronized conditions between the visual doi:10.1111/j.1525-1594.2008.00564.x observation of cavitation and the emitting of an acoustic signal.…”
mentioning
confidence: 99%